Consequences of Untreated Pediatric Trigger Thumb: Case Report. (May 2022) - Rao, Vinay; Ericson Jr, William B.
Pediatric trigger thumbs present a conundrum for hand surgeons. Surgery for trigger thumbs has inherent risks, such as infection, nerve injury, and the risks of anesthesia, but will reliably solve the problem. But is surgical intervention necessary? Would these cases resolve spontaneously, eventually, without intervention? If not, what are the long-term consequences of the inability to fully extend the thumb interphalangeal joint? We present a pediatric trigger thumb that was symptomatic for 22 years, with complete resolution of symptoms after surgical intervention. This report illustrates at least some pediatric trigger thumbs will not resolve without surgical intervention, but treatment, even after 21 years, can result in normal thumb motion and function.